1990
DOI: 10.1159/000153900
|View full text |Cite
|
Sign up to set email alerts
|

GC Subtyping and HIV Infection in a Spanish Population: No Evidence of an Association between GC Subtypes and AIDS

Abstract: Group-specific component (GC) subtyping was performed by isoelectric focusing in 318 Spanish drug users at risk for infection or infected by HIV (85 HIV se-ronegatives, 111 HIV seropositives without symptoms, 89 seropositives with symptoms, 33 AIDS patients) and 187 healthy individuals. There was no significant association between GC subtypes and susceptibility to HIV infection and/or progression to AIDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…The lack of association of VDBP locus variants with progression is in accordance with previous studies (Alonso et al, 1990;Cleve et al, 1988) discarding the earlier described association of VDBP variability with susceptibility to HIV-1 infection and progression to AIDS (Eales et al, 1987). In addition, our findings also evidence the lack of VDBP locus interaction with the tested vitamin-D pathway genes in the context of HIV-1 infection.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The lack of association of VDBP locus variants with progression is in accordance with previous studies (Alonso et al, 1990;Cleve et al, 1988) discarding the earlier described association of VDBP variability with susceptibility to HIV-1 infection and progression to AIDS (Eales et al, 1987). In addition, our findings also evidence the lack of VDBP locus interaction with the tested vitamin-D pathway genes in the context of HIV-1 infection.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies revealed the association between CYP27B1 polymorphisms and immune related diseases, such as Hashimoto's thyroiditis, Graves' disease and type 1/2 diabetes (Lopez et al, 2004) and Addison's disease (Jennings et al, 2005). VDBP polymorphisms have been associated with HIV-1 infection (Eales et al, 1987) but these findings have not been replicated (Alonso et al, 1990;Cleve et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Fracture risk OR for Gc2-2 = 0.32 (CI = 0.13–0.80) Compared to the other genotypes, none of the Gc2-2 individuals had any low energy fractures ( p  = 0.021).Papiha et al86 2621United KingdomCaucasianGc1F, Gc1S, Gc2; Variable tandem (TAAA) n - Alu repeat in Intron8Intron 8* Alu repeat had significant association with lumbar spine and femoral neck BMD. BMD was observed to be lower in men with 10/8 genotype than 10/10 genotype ( p  < 0.05).SarcoidosisMilman et al192 4444DenmarkCaucasian a Gc1F, Gc1S, Gc2NS Infections Diseases Human Immunodeficiency Virus (HIV)Alonso et al216 318 (at risk or infected)187SpainCaucasianGc1F, Gc1S, Gc2NSCleve et al217 971523United KingdomCaucasian a Gc1F, Gc1S, Gc2NSEales et al219 203 (at risk males)177 (50 homo-sexual and 122 hetero-sexual males)United KingdomCaucasian a Gc1F, Gc1S, Gc230% of AIDS patients were homozygous for Gc1F compared to 0.8% of controls ( p  < 0.0001). Gc2-2 individuals were overrepresented in sero-negative contacts of AIDS patients ( p  < 0.05).Pronk et al212 447 (96 AIDS patients and 351 homosexual men86NetherlandsCaucasian a Gc1F, Gc1S, Gc2NSPutkonen n et al218 125 (85 AIDS patients and 40 couples with 1 infected partner)3394SwedenCaucasian a Gc1F, Gc1S, Gc2N...…”
Section: Introductionmentioning
confidence: 99%